Implementasi Religiusitas dan Marketing Mix Terhadap Keputusan Pembelian Kosmetik Halal - Sarah Shabrina; Prilla Kurnia Ningsih (Tauhidinomics: Journal of Islamic Banking and Economics, 2026)
This research is intended for halal cosmetics industry players to be able to see in terms of religiosity and marketing mix in making purchase decisions. In this study, there are five independent variables that are studied, namely, religiosity, halal label, product quality, price and e-wom. Meanwhile, the dependent variable is the purchase decision. The study was conducted on 100 gen z women living in the Greater Jakarta area. The method used in this research is a quantitative method with the sem-pls data analysis method in the smart-pls 4.0 application. The results showed that the variables of religiosity and product quality could affect consumer purchase decisions, while the variables of halal labels, prices and e-WOM had no effect on consumer purchase decisions.